Indigenous knowledge and its infusion into ordinary level science learning at one secondary school in Zimbabwe - Chikuvadze, Pinias; Jatakulula, Kenmore (Advanced Research Journal, 2025)
Zimbabwe’s curriculum framework (2024 - 2030) stresses the need for science learning activities to be grounded in cultural knowledge. Despite this recognition, the infusion of Indigenous Knowledge (IK) into science learning remains limited at the selected secondary school. In this context, this sought to gain insight into the extent to which the teachers are infusing IK into their Ordinary Level Science learning activities. The study was grounded in a qualitative approach, and data was sourced from the seven purposively sampled participants (teachers). Data was generated through the literature method and interview protocol and analyzed thematically. The findings of the study revealed that the participants (teachers) had a clear understanding of IK as a concept and its relevance in learning activities. It was also acknowledged that the participants were using the student-centred approaches to infuse IK into ordinary level science learning activities. However, the participants encountered numerous challenges when infusing IK into science learning activities. From the highlighted findings, it was concluded that despite the existence of some challenges, the participants were, to a larger extent, infusing IK into ordinary level science learning activities at the selected school. We recommend that further research be conducted into the challenges faced when infusing IK into learning with the view of refining instructional methods.
Keywords: Ordinary level science; Indigenous knowledge; infusion; learning activities; Zimbabwe